ECONOMIC ANALYSIS OF CONVERSION OF LAND FUNCTION FOR RICE PICE AGRICULTURE IN SIMALUNGUN DISTRICT (Case of Pamatang Simalungun Village, Rambung Merah, Karang Bangun and Siantar Estate, Siantar District, Simalungun Regency) - Hamat Sarif Batubara; Diana Chalil; Sri Fajar Ayu (CV. Radja Publika, 2024)
The conversion of wetland rice farming land is one of the phenomena of changing lowland rice farming land into other food crops and horticultural crops. The aim of this research is to examine the economic value of land before and after land conversion, and analyze the impact of agricultural land conversion on farmers' income, as well as find out what factors influence land conversion. This research uses a case study method, where to answer the research objectives using multiple linear regression analysis, land rent value, farmer income, R-square test, F test, and T-test using the EViews 12 software application. The research results show the value The average land rent for respondents' agricultural land is IDR 24,771,425/year. Based on the classification of agricultural land, the average land rent for respondents for lowland rice crops is IDR 5,920/m²/year, and the average land rent for respondents for other food crops and horticulture is IDR 7,287/m²/year. For respondents, the average farming income was IDR 38,743,925/year, and based on agricultural land classification, the average yield of wetland rice was IDR 7,370/m²/year, as well as other food and horticultural crops of IDR 24,231/m²/year. . Based on the results of the regression analysis, the R-square value was obtained at 0.897970, which means that the independent variable explains the change of function of paddy fields in Simalungun Regency by 89.79%, while the remaining 10.21% is influenced by other variables outside the research. The results of the F test (simultaneous) show that all independent variables have a significant effect on the dependent variable with a probability value (F-statistic) of 0.000000 < 0.05, and partially the factors that have a significant effect on land conversion are land area before conversion and acceptance after the change of function as a farmer, while other variables, namely age of the farmer, last education of the farmer, income before the change of function, operational costs before the change of function and operational costs after the change of function have no significant effect (the influence of the variables is very small).